2008
DOI: 10.1175/2008jtecha1113.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of DBS Wind Measurement Technique in Different Beam Configurations for a VHF Wind Profiler

Abstract: Atmospheric winds in the troposphere have been observed routinely for many years with wind profiling (VHF and UHF) radars using the Doppler beam swinging (DBS) technique. Accuracy of wind estimates using wind profiling radars with different beam configurations has its limitations due to both the system of observation and atmospheric conditions. This paper presents a quantitative analysis and evaluation of horizontal wind estimation in different beam configurations up to an altitude of 18 km using the mesospher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Wind velocity measurements were carried out with the Doppler beam-swinging (DBS) technique Rao et al, 2008) with an elevation angle from vertical of 28 • , with a sampling frequency of 1 Hz and with the range gates centered at 11 vertical heights (40, 50, 60, 80, 100, 120, 140, 150, 160, 180, 200 m). The profiler lidar was deployed at the location referred to as the lidar supersite (Fig.…”
Section: Experimental Setup and Measurement Proceduresmentioning
confidence: 99%
“…Wind velocity measurements were carried out with the Doppler beam-swinging (DBS) technique Rao et al, 2008) with an elevation angle from vertical of 28 • , with a sampling frequency of 1 Hz and with the range gates centered at 11 vertical heights (40, 50, 60, 80, 100, 120, 140, 150, 160, 180, 200 m). The profiler lidar was deployed at the location referred to as the lidar supersite (Fig.…”
Section: Experimental Setup and Measurement Proceduresmentioning
confidence: 99%
“…As other nonradar wind measurement techniques become more accurate, and the need for improved accuracy of wind measurements for incorporation into numerical forecast models develops, MST radars must keep pace, and so the accuracy of the various radar methods of wind measurement must be continually re-addressed. For example, Luce et al (2001b) compared radar and radiosonde measurements just prior to 2001, and even in 2008, Rao et al (2008a), and references therein, have once again examined the reliability of the DBS method. We will not dwell on these issues here, but they may arise as special subtopics in the following subsections.…”
Section: Horizontal Windsmentioning
confidence: 99%
“…A comparison shows that their results are highly consistent with our results, as shown in Figure 9 and Table 4, although the VAD method that we use to estimate the horizontal wind velocity is very different from DBS method that they employed, and the time resolutions of our data (5 min and 10 min) are also different from those (40 min and 60 min) that they used. Rao et al [30] compared the horizontal wind velocities measured by a 53 MHz Gadenki VHF radar with rawinsonde measurement to evaluate the performance of the DBS technique with different beam configurations in horizontal wind velocity measurement. They found that the standard deviation for a four-beam configuration varied from 1.4 to 2.5 ms −1 , which is very consistent with the result (1.897 ms −1 for the 52 MHz VHF radar) obtained in this study.…”
Section: Comparisons Between Radar Winds and Rawinsonde Windsmentioning
confidence: 99%
“…Although the rawinsonde-measured horizontal wind velocity has long been employed to serve as the standard reference to assess the accuracy and precision of the wind velocity measured by wind profilers for academic research and weather/meteorological applications (e.g., [18,30]), theoretical analysis and radar experiments have shown that the precision of the rawinsonde-measured horizontal wind velocity may not be better than that of the radar measurement using the DBS method [31]. However, systematic evaluations of the precision and accuracy of the VAD-deduced wind velocities measured by wind profilers operated at different frequencies in different environments are not documented.…”
Section: Introductionmentioning
confidence: 99%